PENGARUH PENGGUNAAN APLIKASI PEMBELAJARAN INTERAKTIF DAN AKUN BELAJAR. ID TERHADAP PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK - Supratman Jayadi; Isnaini, Isnaini; Candra, Candra; Aliahardi Winata (Irfani, 2025)
This study aims to analyse the effect of using interactive learning applications and Belajar.id accounts on improving student motivation, as well as to examine how the integration of both can shape adaptive and sustainable learning motivation in the context of 21st-century digital learning. This study employs a quantitative approach using a survey method. The research subjects are students from Class IX A of SMP Plus Miftahul Falah who actively use the Belajar.id account and interactive learning applications in their learning activities. The instrument used is a closed-ended questionnaire with a five-point Likert scale. Data analysis was conducted using descriptive statistical tests, normality tests, and multiple linear regression with the assistance of SPSS software. The results of the study indicate that both the use of interactive learning applications (X₁) and the utilisation of the Belajar.id account (X₂) have a significant influence on students' learning motivation (Y). Variable X₁ contributed 34.2% to Y, with a regression coefficient of 0.804 (p < 0.05), while variable X₂ contributed a larger 37.8%, with a regression coefficient of 0.582 (p < 0.05) and a beta value of 0.615. These findings indicate that the integration of digital technology in the learning process can significantly enhance students' learning motivation. Therefore, the use of digital-based learning technologies such as interactive applications and Belajar.id accounts needs to be continuously developed to support a more effective, engaging, and relevant learning transformation in line with the demands of education in the digital age.